2009
DOI: 10.1016/j.psyneuen.2009.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Neurosteroids’ effects and mechanisms for social, cognitive, emotional, and physical functions

Abstract: SummaryHormones are trophic factors that integrate central and peripheral nervous system functions, and can influence social, cognitive, emotional and physical (SCEP) processes. Greater understanding of behavioral and neurobiological underpinnings of mental, cognitive, and/or physical changes with maturation is becoming increasingly important as the world's population ages. There are individual differences in how people age, but the factors that influence these differences are not well understood. Social suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 203 publications
2
58
0
1
Order By: Relevance
“…Besides dihydrotestosterone (DHT) synthesis, 5α-R is the rate-limiting enzyme in the biosynthesis of 3α,5α-reduced neurosteroids (3α,5α-NS), such as allopregnanolone (AlloP). 3α,5α-NS modulate emotional responses and cognitive function (Frye, 2009;Paris et al, 2011b), which are mediated in part by the PFC (Davidson, 2002;Paris et al, 2011b). With this in mind and the finding that short-term exposure to BPA affects 5α-R levels in the PFC of adult female rats (Castro et al, 2013b), we believe that this enzyme might be a potential target for BPA-mediated effects in the female perinatal brain.…”
Section: Introductionmentioning
confidence: 91%
“…Besides dihydrotestosterone (DHT) synthesis, 5α-R is the rate-limiting enzyme in the biosynthesis of 3α,5α-reduced neurosteroids (3α,5α-NS), such as allopregnanolone (AlloP). 3α,5α-NS modulate emotional responses and cognitive function (Frye, 2009;Paris et al, 2011b), which are mediated in part by the PFC (Davidson, 2002;Paris et al, 2011b). With this in mind and the finding that short-term exposure to BPA affects 5α-R levels in the PFC of adult female rats (Castro et al, 2013b), we believe that this enzyme might be a potential target for BPA-mediated effects in the female perinatal brain.…”
Section: Introductionmentioning
confidence: 91%
“…Young rats, which have higher allopregnanolone levels in the cortex (proestrous and late pregnancy), have been shown to exhibit better performance on the object recognition task than diestrous rats or rats in early pregnancy (Frye, 2009). Similarly, other studies have indicated that allopregnanolone can improve memory impairment and inhibit the symptoms of aging and neurodegenerative diseases.…”
Section: Article In Pressmentioning
confidence: 97%
“…Recognition of its importance has fundamentally changed endocrinology in recent decades. In the brain, locally produced steroids are called neurosteroids (240,477,478,611). In anthropoid primates, the adrenal glands are a major source of precursor molecules for local steroid synthesis.…”
Section: Neuroendocrine Backgroundmentioning
confidence: 99%